Shock Wave Analysis at Signalized Intersections (Case Study: Jl. R. Saleh S. Bustaman – Jl. Raden Aria Wiranata) - Guterres, Eurico Da Silva; Rulhendri, Rulhendri; Chayati, Nurul (ASTONJADRO, 2026)
This study analyzes shock waves at a three-signal intersection on Jalan R. Saleh S. Bustaman and Jalan Raden Aria Wiranata, which is a crucial point in traffic flow in urban areas. Population growth and urbanization increase the need for transportation infrastructure improvements. This study aims to understand the effect of traffic signals on vehicle flow, density, and speed, and analyze the queue lengths that occur during traffic light changes. The research method uses direct observation to collect data on traffic flow, vehicle speed, and traffic light duration. The results of the analysis show a mathematical relationship between the flow, density and highest speed at the research location, obtained maximum density (Dm) on Friday of 173.14 smp / km, Maximum speed (Sm) of 6.193 km / hour, Maximum volume (Vm) of 1072 smp / hour and taken the condition of the flow VA = 628.8 smp / hour which experienced a delay of 105 seconds obtained the queue length (Qm) is 78 meters and the normalization time required is 0.013 seconds much smaller than the duration of the green light which is 25 seconds. This means that when the light changes from green to red all vehicles queuing have passed the stop line. The performance of traffic lights until compared to the condition VA = 847.2 smp / hour experienced a queue length of 4300.86 meters and required a normalization time of 9.01 seconds which is still smaller than the duration of the green light of 25 seconds. This means that when the light changes green to red all vehicles queuing have passed the stop line. The conclusion of this study confirms that efficient traffic signal management can reduce congestion and improve road safety.